Enforcement against wildlife crimes in West Malaysia: the challenges - Ariffin, Mariani (Penerbit Universiti Malaysia Terengganu, 2015)
This paper investigates challenges facing the enforcement of wildlife conservation law in West Malaysia. The study used information stemming from desk-based research and interviews with key informants from wildlife enforcement agencies as well as several environmental NGOs. The interviews were carried out using semi-structured questions to examine key informants’ views about the main challenges hampering the effective enforcement of wildlife conservation law in the region. The study revealed that all interviewees concur that insufficient institutional capacity in terms of manpower, skills and equipment is the main challenge to wildlife enforcement. Other major challenges were public cooperation as well as inter-agency cooperation and coordination. Apart from that, respondents from NGOs perceived lack of political-will as another major challenge facing the enforcement of wildlife conservation law, though no mention of this was made by the enforcement agencies. The study provides practical insights into some aspects of the enforcement challenges of wildlife conservation in West Malaysia. These insights may help decision-makers at the local and national levels to consider some measures to overcome the challenges faced by the wildlife enforcement agencies to ensure better wildlife conservation in general.